2020
DOI: 10.2334/josnusd.19-0373
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological mechanisms of persistent orofacial pain

Abstract: Nociceptive stimuli to the orofacial region are typically received by the peripheral terminal of trigeminal ganglion (TG) neurons, and noxious orofacial information is subsequently conveyed to the trigeminal spinal subnucleus caudalis and the upper cervical spinal cord (C1-C2). This information is further transmitted to the cortical somatosensory regions and limbic system via the thalamus, which then leads to the perception of pain. It is a well-established fact that the presence of abnormal pain in the orofac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 86 publications
1
19
0
1
Order By: Relevance
“…Also, after NGF/GDNF treatment the number of SGCs appears to be smaller than in control, at least in the illustrated sections. There is evidence that SGCs in sensory ganglia play functional roles under both normal and pathological conditions and contribute to hyperalgesia (Jasmin et al 2010;Hanani & Spray, 2020;Shinoda et al 2020) and therefore may participate in the production of hyperalgesia described in this paper. Moreover, it was found that pERK is upregulated in SGCs (as well as in neurons) in sensory ganglia in pain models, and contributes to pain states (Takahashi et al 2006;Sugawara et al 2017;Song et al 2018;Yamakita et al 2018;Zhang et al 2020).…”
Section: Letter To the Editormentioning
confidence: 69%
“…Also, after NGF/GDNF treatment the number of SGCs appears to be smaller than in control, at least in the illustrated sections. There is evidence that SGCs in sensory ganglia play functional roles under both normal and pathological conditions and contribute to hyperalgesia (Jasmin et al 2010;Hanani & Spray, 2020;Shinoda et al 2020) and therefore may participate in the production of hyperalgesia described in this paper. Moreover, it was found that pERK is upregulated in SGCs (as well as in neurons) in sensory ganglia in pain models, and contributes to pain states (Takahashi et al 2006;Sugawara et al 2017;Song et al 2018;Yamakita et al 2018;Zhang et al 2020).…”
Section: Letter To the Editormentioning
confidence: 69%
“…Previous study suggested that the expression of toll-like receptor 4 and IL-1β are increased on day 1 following tooth pulp exposure [22]. On the other hand, macrophage accumulations are caused in the trigeminal ganglion followed orofacial inflammation, and the accumulated macrophages secretes neuromodulators to drive ectopic and chronic pain by inducing neuronal and synaptic plasticity [8][9][10]12]. To examine the changes in expression of toll-like receptor 4, IL-1RI, Iba1, and IL-1β in trigeminal ganglion after tooth pulp exposure, immunohistochemistry was performed following operations of sham or tooth pulp exposure.…”
Section: Expression Of Toll-like Receptor 4 Il-1ri Iba1 and Il-1β mentioning
confidence: 99%
“…Persistent orofacial pain following trigeminal nerve injury or orofacial inflammation causes a variety of motor and sensory disorders in the orofacial area, including masticatory deficits and/or dysphagia [5]. Recent pain studies indicated that one of the factors that can induce such symptoms is long-term sensitization of peripheral nerves and enhancement of nerve excitability, resulting in hypersensitivity of the peripheral and central nervous system [6][7][8][9]. However, the detailed mechanism of how the peripheral nervous system is associated with the development of orofacial-referred pain following tooth pulp inflammation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In the chronic setting, these cells ironically facilitate pro-nociceptive activity and fuel sensations of pain. [67][68][69][70] In their activated state, these immune cells upregulate the expression of translocator proteins (TSPOs) in pathologic conditions. This molecular feature is relatively unique when compared with other cell types and has been exploited as a means of identifying these cells in vivo.…”
Section: Pet Imaging Of Activated Glial Cells and Macrophagesmentioning
confidence: 99%